2016
DOI: 10.1186/s13167-016-0060-8
|View full text |Cite|
|
Sign up to set email alerts
|

Antarctica challenges the new horizons in predictive, preventive, personalized medicine: preliminary results and attractive hypotheses for multi-disciplinary prospective studies in the Ukrainian “Akademik Vernadsky” station

Abstract: BackgroundAntarctica is a unique place to study the health condition under the influence of environmental factors on the organism in pure form. Since the very beginning of the scientific presence of Ukraine in the Antarctic, biomedical research has been developed for the monitoring of individual biomarkers of winterers and medical accompaniment in Antarctic expeditions. The aim of the study was to analyze and discuss the retrospective data of long-term monitoring and observations in Ukrainian Antarctica statio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 33 publications
1
29
0
6
Order By: Relevance
“…Our preliminary results demonstrated changes in the spleen size in all participants after 1-year Antarctic expeditions with a tendency to deacrese after returning (this was also observed in the liver and thyroid gland size) [141]. Inordinate splenic erythropoiesis can be initiated e.g.…”
Section: Role Of Spleen-associated Biomarkers In Patient Stratificatisupporting
confidence: 60%
See 1 more Smart Citation
“…Our preliminary results demonstrated changes in the spleen size in all participants after 1-year Antarctic expeditions with a tendency to deacrese after returning (this was also observed in the liver and thyroid gland size) [141]. Inordinate splenic erythropoiesis can be initiated e.g.…”
Section: Role Of Spleen-associated Biomarkers In Patient Stratificatisupporting
confidence: 60%
“…Skin mycobiome plays importnt role in shaping innate and adaptive immunity in health and disease [123,140]. Recent studies in the unique setting of the Antarctic have shown an increase in fungi on the skin in expedition participants,believed to be due to interferences with local immunity and dysbiosis of the normal skin microbiome due to stress, recycled air and antiseptic agents [141]. Akkermansia muciniphila is believed to have an important function in the pathogenesis of IBD and obesity; therefore, Akkermansia muciniphila, which is an indicator of health status, may be a key node for psoriasis as well as IBD and obesity [142].…”
Section: Skin Microbiomementioning
confidence: 99%
“…Pain diagnostics and treatment are highly individual involved in a wide spectrum of suboptimal health conditions, early and advanced stages of developing pathologies and collateral diseases such as CVD, NNND, diabetes, and cancer. Application of PPPM concepts to advanced pain management demands multidisciplinary expertise considered in the context of improved health care economy and policy and direct benefits to the patient [4547]. …”
Section: Predictive Preventive and Personalised Medicine (Pppm)mentioning
confidence: 99%
“…Unfortunately, environment is still a largely neglected topic in health care. PPPM approach aims to develop an appropriate knowledge and technological skills for promoting affordable strategies in the emerging fields of environmental risk factors, epidemiology, healthy lifestyle, individualised nutrition, food technology and culture in a framework of cost-effective health care [29, 47, 5355]. …”
Section: Predictive Preventive and Personalised Medicine (Pppm)mentioning
confidence: 99%
“…Проблемою адаптації до екстремальних умов життєдіяльності українських зимівників займається група науковців (медиків, фізіологів, психологів) Національного антарктичного наукового центру впродовж тривалого часу. Вони довели, що у процесі адаптації в період зимівлі змінюється не тільки індивід, а й середовище, внаслідок чого між ними встановлюється відношення адаптивності, не завжди врівноважене, оскільки експедиційна діяльність пов'язана з впливом на зимівників численних екстремальних чинників (особливості регіональної фотоперіодики, зсув часових поясів, сенсорна депривація, активація метео-та геліофізичних явищ тощо), що створює додаткове навантаження на функціональні системи організму (Moiseienko, Sukhorukov, Pyshnov, Mankovska, Rozova, Miroshnychenko et al, 2016).…”
Section: результати та дискусіїunclassified